2020
DOI: 10.1177/1060028020963645
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hyperoncotic Albumin on Duration of Vasopressor Support in Septic Shock: A Propensity Score–Matched Analysis

Abstract: Background While albumin has not been shown to reduce mortality in sepsis and septic shock, a tertiary analysis of a large trial suggested that it may reduce the duration of vasopressor use in septic shock. Objective We sought to test if 25% albumin administration was associated with reduced cumulative vasopressor use in septic shock in a real-world setting. Methods This was a retrospective, propensity score–matched cohort study of septic shock in which patients receiving albumin were compared with a matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…As we know, albumin is similarly associated with outcomes in sepsis and septic shock; randomized controlled trials in this field could be a start 17 , 21 . The controversial results of studies and meta-analyses in this field may be explained by heterogeneous patient populations and the time sensitivity of this treatment 22 .…”
Section: Discussionmentioning
confidence: 99%
“…As we know, albumin is similarly associated with outcomes in sepsis and septic shock; randomized controlled trials in this field could be a start 17 , 21 . The controversial results of studies and meta-analyses in this field may be explained by heterogeneous patient populations and the time sensitivity of this treatment 22 .…”
Section: Discussionmentioning
confidence: 99%
“…As we know, albumin is similarly associated with outcomes in sepsis and septic shock; randomized controlled trials on this eld could be a starting block 15,17 . The controversial results of studies and meta-analyses on this eld may be explained by heterogeneous patient populations and the time sensitivity of this treatment 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The randomized controlled trial ALBIOS showed an improvement in time to suspension of the administration of vasopressor or inotropic agents ( P = 0.007) with administration of 300 mL 20% albumin solution (73). One retrospective, propensity score-matched cohort study of 670 patients in septic shock sought to further evaluate this association (74). While albumin was not associated days alive and free of vasopressors (17.4 vs. 19.4 days, P = 0.160), this study was limited as albumin timing and dose was not protocolized.…”
Section: Interplay Of Fluids and Vasoactive Therapymentioning
confidence: 99%